2014
DOI: 10.1146/annurev-med-022613-090415
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Hospital Readmission Rates: Current Strategies and Future Directions

Abstract: New financial penalties for institutions with high readmission rates have intensified efforts to reduce rehospitalization. Several interventions that involve multiple components (e.g., patient needs assessment, medication reconciliation, patient education, arranging timely outpatient appointments, and providing telephone follow-up), have successfully reduced readmission rates for patients discharged to home. The effect of interventions on readmission rates is related to the number of components implemented, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
377
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 482 publications
(397 citation statements)
references
References 78 publications
(116 reference statements)
12
377
1
7
Order By: Relevance
“…Unfettered access to hospitalization information by way of shared information technology and timely communication of discharge summaries has been demonstrated to improve clinical outcomes primarily by eliminating an important lag time in which lapses in care may occur. [12][13][14] Similarly, hospital-physician continuity of care has been demonstrated to reduce rehospitalizations. 15 Familiarity with the hospital course allows follow-up physicians to determine therapeutic effectiveness and identify complications of hospital therapies or procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfettered access to hospitalization information by way of shared information technology and timely communication of discharge summaries has been demonstrated to improve clinical outcomes primarily by eliminating an important lag time in which lapses in care may occur. [12][13][14] Similarly, hospital-physician continuity of care has been demonstrated to reduce rehospitalizations. 15 Familiarity with the hospital course allows follow-up physicians to determine therapeutic effectiveness and identify complications of hospital therapies or procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The median number of days between the discharge date and the rehospitalization date was 11 (IQR,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). More than four in five (1567 patients or 81%) who were rehospitalized were admitted to the same hospital as their index hospitalization.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…1 Despite widespread efforts using a variety of approaches for reducing readmissions, the effects of readmission reduction programs have been equivocal. [2][3][4][5] In addition, debate continues on the preventability of hospital readmissions, with a systematic review estimating that as few as 27 % of readmissions are truly preventable. 6 The high rate of hospital readmissions and uncertain effects of readmission reduction programs may, in part, stem from incomplete understanding of the reasons for readmission or Electronic supplementary material The online version of this article (doi:10.1007/s11606-016-3764-5) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies have shown that improvements in hospital systems such as organizational culture, including interdisciplinary rounding during hospitalization and at discharge, and optimization of patient care transitions were associated with improved 30‐day outcomes 29, 30, 31. Similarly, other qualitative studies have shown that high‐performing hospitals have specific organizational strategies and enabling structures that distinguish them, including: active communication and coordination among care givers; senior management‐level engagement and support; and an organizational commitment to developing and maintaining a focus on delivering high‐quality care 32, 33.…”
Section: Discussionmentioning
confidence: 99%